Changes of Esophagogastric Junctional Adenocarcinoma and Gastroesophageal Reflux Disease Among Surgical Patients During 1988–2012: A Single-institution, High-volume Experience in China. Issue 1 (January 2016) - Liu, Kai; Yang, Kun; Zhang, Weihan; Chen, Xiaolong; Chen, Xinzu; Zhang, Bo; Chen, Zhixin; Chen, Jiaping; Zhao, Yongfan; Zhou, Zongguang; Chen, Longqi; Hu, Jiankun
Abstract : Objective: To evaluate the changes of esophagogastric junctional adenocarcinoma (EGJA) and gastroesophageal reflux disease (GERD) among surgical patients from 1988 to 2012 in a Chinese high-volume hospital. Background: The incidence of EGJA in Western countries has rapidly increased in recent decades. However, recent data from China remain sparse. Methods: A retrospective analysis was performed on the basis of 5053 patients who underwent surgery for gastric and distal esophageal adenocarcinoma. Total of 1723 patients with EGJA who underwent surgery were included. Changes of the prevalence of GERD and the clinicopathological features and surgical treatment of EGJA were longitudinally analyzed by a 5-year interval. Results: The proportion of EGJA was increased from 22.3% in period 1 (1988– 1992) to 35.7% in period 5 (2008– 2012) ( P < 0.001). The proportion of Siewert type III (35.9% vs 47.0%) ( P < 0.001) and type I (8.7% vs 15.8%) ( P = 0.002) tumors of EGJA was also increased during the past 25 years. The prevalence of GERD had increased gradually from 6.5% in period 1 to 10.9% in period 5 for the 3 subgroups without significant difference ( P = 0.459). There was an upward tendency with significant difference between the proportion of EGJA and the prevalence of GERD ( r = 0.946, P = 0.000). Instead of type II and type III tumors, there was a positive correlation with change in GERD for type I tumors ( r = 0.438, P = 0.029). Total gastrectomy was more preferred among patients with EGJA in period 5 than in period 1 (42.0% vs 19.6%) ( P < 0.001). Conclusions: An increasing trend of EGJA is observed during the past 25 years in West China Hospital. The prevalence of GERD among EGJA had showed a gradually increased trend. However, the causality between GERD and EGJA still needs to be researched further. Total gastrectomy is becoming more preferred procedure in patients with EGJA.